Optimalisasi Peran Perempuan dalam Pengambilan Keputusan politik di Kota Lhokseumawe - Maryam Maryam; Muryali Muryali; Muslem Muslem; Teuku Alfiady; Cut Sukmawati (Jurnal Solusi Masyarakat (JSM), 2026)
According to Statistics Indonesia (BPS), women constituted 50.3% of the total population of Lhokseumawe City in 2025. Despite this demographic majority, their participation in political decision-making remains limited. This situation is attributed to entrenched patriarchal norms, inadequate leadership capacity, limited access to political education, and restricted opportunities to participate in political and governmental institutions. Although Indonesian electoral regulations require political parties to nominate at least 30% women as legislative candidates, the 2024 local legislative election resulted in only 7 of the 25 seats (28%) in the Lhokseumawe Regional House of Representatives (DPRK) being occupied by women, indicating that substantive political representation has yet to reach the expected level. Women's representation in strategic positions within the local government is also limited, with only one female head of a regional government agency serving in 2026. This community empowerment program aimed to strengthen women's political literacy, leadership capacity, advocacy skills, and participation in local political decision-making. The program employed participatory approaches, including Focus Group Discussions (FGDs), political education workshops, leadership mentoring, and policy decision-making simulations. The findings indicate significant improvements in participants' political knowledge, communication and advocacy skills, understanding of public policy formulation, and confidence in engaging in political decision-making forums. The program demonstrates that participatory capacity-building effectively enhances women's political participation and leadership. Sustained mentoring and cross-sector collaboration among local government, universities, political parties, women's organisations, and civil society are recommended to promote more inclusive and gender-responsive political governance in Lhokseumawe City.